Analisis Co-creation dan Self-innovation Terhadap Kinerja Pemasaran PT Semen Baturaja Tbk - Rully Armanto; Muji Gunarto (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of co-creation and self-innovation on the marketing performance of PT Semen Baturaja Tbk. This research method used a quantitative approach with a survey of 58 respondents distributor of PT Semen Baturaja. The research instrument used a questionnaire with data analysis techniques performed by multiple linear regressions. The results showed that co-creation and self-innovation had a positive and significant effect on the marketing performance of PT Semen Baturaja. This partially shows that co-creation has a more dominant influence than self-innovation. The limitation of this research is the relatively small number of samples obtained. A confirmatory study to prove the model formed should use adequate samples. The managerial implications of this research become the basis for policymaking in determining marketing strategies by involving customers (distributors) to be involved in determining the products and marketing strategies carried out. The novelty of this research is the need for co-creation from the company PT Semen Baturaja as the only cement producer in South Sumatra